STRES AKADEMIK DAN OPTIMISME TERHADAP RESILIENSI AKADEMIK PADA MAHASISWA TINGKAT AKHIR - Iffa Alifah; Magdalena Hanoum; Lucky Purwantini (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2022)
The purpose of this study was to examine the relationship and influence of academic stress and optimism on academic resilience. This research is a quantitative research with correlational type involving 91 final year students at Universitas Islam “45” Bekasi. The sampling technique used a non-probability sample technique with a proportionate strafied random sampling technique. This study uses an academic resilience scale with a reliability value of 0.891 Chronbach's Alpha, an academic stress scale with a Chronbach's Alpha reliability value of 0.943 and an optimism scale with a Chronbach's Alpha reliability value of 0.895. The data analysis technique used Rank- Spearman correlation test and multiple linear regression. This study found that there is a positive relationship between academic stress and optimism on academic resilience. Then, there is also an influence between academic stress and optimism on academic resilience with an effective contribution of 13.8% for final year students at Universitas Islam "45" Bekasi.